Problems in implementation gerakan satu rumah satu jumantik (G1r1j) In Mempawah Regency, Kalimantan Barat Province - Tri Isnani (BKM Public Health and Community Medicine, 2021)
Dengue Hemorrhagic Fever (DHF) is still a health problem in Indonesia. One of the programs in controlling dengue fever is Gerakan Satu Rumah Satu Jumantik (G1R1J). G1R1J involved every household active to do mosquito control PSN 3M PLUS. G1R1J as a community empowerment requires an assessment to identify community problems and needs in controlling DHF. Objective. This paper describes the problems in implementing G1R1J from the community, regional government, and stakeholders. Methods The research method was carried out qualitatively. The research was conducted in the East Mempawah Subdistrict, Mempawah Regency, Kalimantan Barat Province in March - November 2019. Data collection techniques were observation, in-depth interviews, and group discussions. Informants were officers from Dinas Kesehatan Kabupaten, Puskesmas, Camat, Lurah, community leaders, and citizens. The data is stored in the form of a transcript and analyzed qualitatively. The validity of the data by triangulasi sources and methods. Results. The need for clean water in this area uses rainfed water. Water is collected in a jar (tempayan) with a capacity of about 500 liters so that if there are larvae, just leave it. There are citizens who refuse fogging and the use of larvicides. Knowledge of DHF, Jumantik, and G1R1J is not yet understood. The special socialization about G1R1J has not been done. There are no G1R1J activities even though the SK already exists. Officers feel a lack of resources and funds. Community activities were in a vacuum, resulting in difficulties in forming the G1R1J organization. Potential as agents of change, midwives who are well-known and close to the community.